Efektifitas Penggunaan Alat Hydraulic Static Pile Driver (HSPD) pada Pemancangan - Elvira Handayani; Jauhar Maknun (Universitas Batanghari, 2018)
The rapid development of construction projects in Indonesia is directly proportional to the tools created and developed to assist and facilitate activities in the work. The tools no longer fully use human power but humans are only a part of the process of operating the tool. Limited land in the city of Jambi became the main reason in the construction of high-rise buildings. Thus, special technology is needed in order to facilitate the implementation of such development. One of the tools used is the tool for foundation work. Deep foundation construction has a more complex structure compared to shallow foundation construction. Therefore, in the construction of high-rise project, the use of jack in pile is considered very appropriate. One of the advantages of jack in pile is environmental disturbance such as vibration and noise can be minimized. In this research will discuss one type of Jack in Pile that is type Hydraulic Static Pile Driver (HSPD). Where in this case the effectiveness of the use of Hydraulic Static Pile Drivers (HSPD) on the Odua Weston project will be discussed according to the literature and supporting data available.Keywords: Effectiveness of Pollution, HSPD, SWOT Analysis